Curriculum Analysis as a Guideline for Learning in Schools: Analisis Kurikulum Sebagai Pedoman Proses Pembelajaran di Sekolah - Sila Monika; Rini Chairunnisa; Siti Aisyah; Abdurrahmansyah (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This research was conducted with the aim of exploring the function of criteria as a reference in the learning process in educational institutions. The approach used in this study was qualitative with a literature review. Data were collected through an analysis of ten references consisting of seven scientific journals and three books related to curriculum studies. Data collection techniques were carried out through documentation, while data analysis was carried out using the content analysis method, which includes the steps of data reduction, data presentation, and conclusions. The findings of this study indicate that the curriculum serves as the primary reference that directs educational objectives, material selection, teaching methods, and assessment of learning outcomes in an integrated education system. However, its implementation still faces various challenges, such as limited teacher capabilities, minimal facilities and resources, and the curriculum's inconsistency with students' needs. Therefore, the success of curriculum implementation depends heavily on the readiness of educators, the availability of adequate facilities, and continuous evaluation.